Szkoła Rzymska. Szkic o jezuickiej eklezjologii i myśli politycznej w przededniu Soboru Watykańskiego I. (Część pierwsza) - WIELOMSKI, Adam (Historia i Świat, 2013)
This article is about the theology of Jesuits in the First Vatican Council (1869-1870). This theology is neo-scholastic and ultramontain, known in the literature as the Roman School. Here's a catholic response to an unstable period of the nineteenth century, full of revolutions andcounter-revolutions. We can point some of characteristics of the Roman School: 1 / recognition a primary act of faith as an irrational. Grace to the decision in favor of the faith, the world can be rationally explained. 2 / Theology is evolutionary, but teleological. 3 / The Bishop of Rome watches over the truth of rational explanations of the world and the development of theology. Pope separates truth from error. For this reason, must be infallible in matters of dogma and needs to have full authority in the Catholic Church.